Psychology in Policy Redefining Politics Through The Individual - Carriere, Kevin R. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book takes an insider perspective of the psychological issues of creating policy. Instead of considering what the products of policy are - often the case in psychological and political science work - this book examines the individual processes present in proposing and engaging with policy. The individual who engages with the policy and its meanings, the individual who resists the policy through conformity, and the individual who writes the policy for their own ideological purposes are all political actors in a psychological system. This book puts forward a cultural political psychology as the psychological study of the process of values, policy, and power dynamics. Through exploring public policy through private policy generation and individual interaction, this book pushes theoretical understandings of policy and activism in new ways. Centering on an individual's own values in facing various policy restrictions from governments, parents, or peers, the importance of examining collective actions and also collective inactions of individuals is noted and expanded on in the text. The book provides applications of its arguments through examining the processes of unionization and actualized democracy. It seeks to point out new research avenues, including the hypogeneralization of values, one's exclusion through activism, and everyday revolutions. This book addresses the centrality of the individual and meaning-making systems when considering where policy, politics, and psychology intersect. This book is primarily addressed to psychologists and political scientists interested in how to make change in public policy. While the experiences within the book are United States-centric, the thoughts and theories behind them are meant to be applicable to a wide variety of political systems. As there is currently very little literature on the topic, this book seeks to fill the gap and offer concise information on such an important dimension of cultural and political psychology. It is expected that the book will be of great interest for researchers in these areas, as well as for graduate-level students. In particular, this book will be relevant to researchers and students working on political psychology, public policy, development, community psychology, social representations, semiotics, activism, and social movements, to name a few.
Introduction -- Moving towards a political cultural psychology -- Value-laden and value-creation: The political process of values -- Private & public policy: The intersection of cultural and societal laws -- The power of inaction: Power dynamics and public policy -- Applications for a cultural political psychology -- Psychology Is Policy: Moving towards a cultural political psychology -- References -- Index. .
Keywords: Psychology; Personality; Difference (Psychology).; Political planning; Community psychology; Economic development; Behavioral Sciences and Psychology; Personality and Differential Psychology; Public Policy; Community Psychology; Development Studies